Raquel Interviews Isolda who Interviews Raquel: A Conversation about Dialogue - Milani, Raquel [UNESP]; Lima, Isolda Gianni de; Mukhopadhyay, S.; Greer, B. (Mathematics Education & Soc, 2015)
In this paper we characterize a mutual interview between two teachers, Raquel and Isolda, about the concept of dialogue in mathematics education. These teachers have developed a collective practice in a supervised teaching practice course on mathematics based on teacher-students dialogue. The interview was important to know what each teacher thought about the concept. This knowledge was used to design the course. Here we present a definition of mutual interview based both on the concept of dialogue (by Alro and Skovsmose, and Bohm), and the concept of interview (by Kvale and Brinkmann), as well as the dialogue experience between Raquel and Isolda. This definition also includes dialogic acts and the actions of seeing, thinking, and constructing common knowledge together.